2001
DOI: 10.1079/bjn2001445
|View full text |Cite
|
Sign up to set email alerts
|

Dietary conjugated linoleic acid (CLA) induces apoptosis of colonic mucosa in 1,2-dimethylhydrazine-treated rats: a possible mechanism of the anticarcinogenic effect by CLA

Abstract: One of the objectives of the present study was to investigate whether 1 % conjugated linoleic acid (CLA) in the diet reduced tumour incidence in the colon of 1,2-dimethylhydrazine (DMH)-treated rats. Colon cancer was induced by injecting 6-week-old, male, Sprague -Dawley rats with 15 mg/kg DMH twice per week for 6 weeks. They were fed either 1 % CLA or a control diet ad libitum for 30 weeks. Dietary CLA significantly decreased colon tumour incidence (P,0 : 05). Our second objective was to investigate whether a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
2
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(61 citation statements)
references
References 37 publications
(36 reference statements)
2
56
2
1
Order By: Relevance
“…CLA treatment inhibits the formation of colonic 2-amino-3-methylimidazo[4,5-f]quinoline (IQ)-DNA adducts and putative precancerous ACF in colon. 18 Recently, Park et al 37 reported that dietary CLA can inhibit 1,2-dimethylhydrazine (DMH)-induced colon carcinogenesis through possibly induction of apoptosis. Cell proliferation is known to play an important role in multistage carcinogenesis with multiple genetic changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CLA treatment inhibits the formation of colonic 2-amino-3-methylimidazo[4,5-f]quinoline (IQ)-DNA adducts and putative precancerous ACF in colon. 18 Recently, Park et al 37 reported that dietary CLA can inhibit 1,2-dimethylhydrazine (DMH)-induced colon carcinogenesis through possibly induction of apoptosis. Cell proliferation is known to play an important role in multistage carcinogenesis with multiple genetic changes.…”
Section: Discussionmentioning
confidence: 99%
“…CLA is known to be a possible chemopreventive agent against ACF formation 18,19 and colon carcinogenesis. 37 Whereas CLA used in published studies 15,17,35,39 contains a mixture of positional and geometrical iso- mers, c9,t11-18:2 isomer is considered to be the active constituent. Therefore, the suppressing effect of BMO on colon carcinogenesis in the current study may be attributed to c9,t11-18:2 isomer derived from c9,t11,t13-18:3 in the BMO diets.…”
Section: Discussionmentioning
confidence: 99%
“…Em 2001, Park et al 48 , estudando câncer de cólon induzido por dimetilhidrazina em ratos, demonstraram que a redução da incidência do câncer está relacionada com o aumento do índice apoptótico. Posteriormente, o mesmo grupo demonstrou que o aumento do índice apoptótico estaria relacionado, em parte, com a redução de prostaglandinas E2, acompanhada do aumento da razão das proteínas pró-apoptóticas Bax/Bcl-2, como foi observado pelos autores 49 .…”
Section: Cla E Câncerunclassified
“…Studies in cell lines have shown that CLA inhibits the growth of a variety of tumour cells (95 -97) . Dietary CLA has also been shown to reduce colon cancer incidence in animals administered a colorectal carcinogen (98) . In a human epidemiological study in which CLA intakes were estimated, high CLA intakes were associated with a reduced risk of CRC; the RR associated with the highest v. the lowest quartile of intake was 0·71 (95 % CI 0·55, 0·91; P for trend ¼ 0·004) (99) .…”
Section: Potential Chemopreventive Agents In Dairy Foodsmentioning
confidence: 99%